PERENCANAAN PROGRAM PENINGKATAN PEMASARAN HASIL PRODUKSI PERTANIAN/PERKEBUNAN DI KOTA BATU - Maria Theresia Dian Kartikawati; Mardiyono .; Mochamad Makmur (REFORMASI, 2015)
The increase of quality and quantity of the most agricultural product in Batu City doesn’t generate farmer’s welfare. It is indicated by the decrease of Gross Regional Domestic Product (GRDP) percentage on the agriculture sector annually. It is assumed that the condition caused by marketing planning system. The research uses a descriptive method with a qualitative approach. Result of the research shows that the planning process in Batu City uses political, technocratic, participative and top-down and bottom-up approach. The planning process comprises the stages of investigation, problem formulation, resources identification, aim and target determination, work planning formulation, and budgeting.Key stakeholders who influence the planning process are the Batu City Mayor, Batu City Local Parliament and Batu City Agricultural and Forestry Agency, although society has also been involved. The program planning supporting factors are potential Batu resources, government policies that support funding factors, as well as the presence of mass media and universities. Inhibiting factors include socio-cultural attitudes that are difficult to accept change, the quality of the planning human resources that still need some improvement, lack of supporting data in the planning process, yet the evaluation of the impact, as well as global market conditions tighten competition marketing of agricultural products